Labores agroecológicas y agrotécnicas en el cultivo de aguacate (Persea americana Mill.) - Flores León, Jonathan Joel (2022)
The present investigation details the agroecological and agrotechnical tasks in the cultivation of avocado (Persea americana Mill.). This fruit is consumed by all Ecuadorians and every day it has greater acceptance in the national market, which has encouraged its cultivation; however, the concentration of the production of the most cultivated variety “Fuerte” has repercussions in low prices of the fruit at the producer level according to the climatic conditions and the different agrotechnical tasks of the crop. The conclusions determine that the good agro-environmental conditions in the avocado-producing areas favor the development of the tree and the obtaining of fruit practically throughout the year, as well as a continuous overlapping of the different phenological phases of the tree; promote the planting of the avocado crop in the optimal areas for its development, with rainfall from 600 to 900 mm, and the crop prefers loam or sandy loam soils with pH 5,5-7,5 and the benefits of avocado establishment, consist in carrying out all the agrotechnical tasks from soil preparation, excellent seed, pruning, irrigation, fertilization, pest and disease control, tutoring during the first years, so that the crop obtains optimal yields.